Gene Mining and Genetic Effect Analysis Reveal Novel Loci, TaZn-2DS Associated with Zinc Content in Wheat Grain - Zhuangzhuang Hong; Zhankui Zeng; Jiaojiao Li; Xuefang Yan; Junqiao Song; Qunxiang Yan; Qiong Li; Yue Zhao; Chang Liu; Xueyan Jing; Chunping Wang (Agriculture)
Zinc is an essential microelement of enzymes and proteins in wheat grains and humans. A deficiency in zinc content can lead to decreased wheat yield and low zinc content in grains, which in turn leads to insufficient dietary zinc intake. One recombinant inbred line (RIL) population derived from crosses Avocet/Huites (AH population) was used to map QTL for grain zinc content (GZnC) using diversity array technology (DArT). Nine QTLs were identified on chromosomes 2D, 3B, 4A, 4D, 5A, 5B, 6A, 7A, and 7D. Among them, QGZn.haust-AH-2D was detected in multiple environments, accounting for 5.61% to 11.27% of the phenotypic variation with a physical interval of 13.62 Mb to 17.82 Mb. Meanwhile, a genome-wide association study (GWAS) (CH population) comprising 243 cultivars or advanced lines revealed some genetic loci associated with zinc content in the wheat 660K single-nucleotide polymorphism (SNP) array. This was also identified within the physical interval of 13.61 Mb to 15.12 Mb of chromosome 2D, which accounted for 8.99% to 11.58% of the phenotypic variation in five models. A high-throughput competitive allele specific PCR (KASP) marker was developed, which verified the wheat natural population (NA population). QGZn.haust-AH-2D was fine mapped into a narrow region named TaZn-2DS between KAZn-2D-3 and 1111273 at a physical distance of 2.70 Mb, and the genetic effect of TaZn-2DS was 11.43%. This study shows that TaZn-2DS is associated with zinc content, and develops KAZn-2D-3 markers for the genetic improvement of nutritional quality in wheat.